Unmasking the relocation experiences of urban poor in Pinagsama Villages, Taguig, Metro Manila - Pinlac, Peter Louie Manganti (Animo Repository, 2011)
This study described the relocation experiences of selected relocatees in Taguig, Metro Manila. This study looked into the factors that influenced the experience of urban poor relocatees’ at the Pinagsama Villages,Taguig, Metro Manila. The quantitative approach was used in the study with the use of the survey. Sixty (60) respondents were gathered who were relocated to the Pinagsama Villages for more than a year. A semi-structured instrument was used to gather the data. The findings revealed that the respondents were of 25 to 70 years old, most are nondegree holders, and majority of them employed as seasonal workers. For their reasons for relocations, most of the respondents transferred to the Pinagsama Villages involuntarily. Different services were provided in the areas which were provided by different agencies. The different agencies consisted of the local government units, non government organizations, private institutions, and people’s organizations. These institutions were active in providing such services which were classified as physical, psycho-social, and economic. The other part of the study evolved around the different relocation experiences of the respondents. The study found that psycho-social areas and political domains were improved while the economic arenas have mixed perceptions. Different factors were also gathered from the socio-demographic and economic characteristics of the relocatees to determine if they have an influence on their relocation experience. Even their reasons for relocations and the types and services provided were also checked to identify if they have influence on their relocation experiences. The study found that education and household size have effects on psycho-social areas and the political domain of their relocation respectively. Lastly, the presence of services provided by different institutions in the area increased their appreciation of their relocation in the Pinagsama Villages.